2008
DOI: 10.1007/s10725-008-9344-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root applied 24-epibrassinolide on carbohydrate status and fermentative enzyme activities in cucumber (Cucumis sativus L.) seedlings under hypoxia

Abstract: The effects of 24-epibrassinolide (EBR) added to nutrient solution on growth of cucumber (Cucumis sativus L.) under root-zone hypoxia were investigated. Cucumber seedlings were hydroponically grown for 8 days in normoxic and hypoxic nutrient solutions with and without addition of EBR at 1 lg l -1 . EBR exerted little influence on plant performance in the normoxic nutrient solution, while the chemical alleviated root-zone hypoxia-induced inhibition of root and shoot growth and net photosynthetic rate (Pn). EBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In this regard, pyruvate decarboxylase (PDC) and alcohol dehydrogenase (ADH) are considered as important plant proteins for coping with hypoxia-induced cellular damage [81]. According to Kang et al [82], 24-epibrassinolide (EBR) further enhances ADH activity in hypoxic cucumber roots. Therefore, PDC and ADH were analyzed by western blotting to verify the proteomic data.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, pyruvate decarboxylase (PDC) and alcohol dehydrogenase (ADH) are considered as important plant proteins for coping with hypoxia-induced cellular damage [81]. According to Kang et al [82], 24-epibrassinolide (EBR) further enhances ADH activity in hypoxic cucumber roots. Therefore, PDC and ADH were analyzed by western blotting to verify the proteomic data.…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al [27] found that the total soluble and starch content of cucumber leaves increased significantly under hypoxic stress because of decreased sugar transport from leaves to roots. Our previous study also found that root-zone hypoxic stress decreased the biomass of plants and soluble protein of leaves [33].…”
Section: Discussionmentioning
confidence: 99%
“…And the previous results showed that exogenous application of BRs to leaves of salt-stressed cotton plants regulated leaf physiology and had little effect on the roots (Shu et al 2011). Kartal et al (2009) found that homobrassinolide (HBL) increased primary root growth during barley germination stage, and Kang et al (2009) reported that root-applied epibrassinolide (EBL) alleviated oxidative damage induced by root-zone hypoxia in cucumber seedlings. Therefore, a root application of BRs might be the most effective to improve cotton salt tolerance.…”
Section: Introductionmentioning
confidence: 99%